Menganalisis Struktur Batin dan Struktur Fisik Puisi “SEBUAH JAKET BERLUMUR DARAH” Karya Taufiq Ismail - Annisa Al Dhira Jahra; Hana Ghina Hanifah (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2025)
This research was motivated by the researcher's curiosity about the poetry of Taufiq Ismail, he is known as a poet of demonstration poetry. The poem with the title "A Jacket Stained With Blood" has a unique choice of words and the symbols contained in the poem that are interesting to study in order to obtain a complete meaning. The formulation of the problem that researchers analyze in this research is what is the inner structure and physical structure embedded in the poem? The aim of this research is to describe the inner structure, namely theme, tone and feeling, atmosphere, and message. By focusing on analyzing the structure of the inner content of the poem concretely and clearly. The method prepared by the researcher is descriptive qualitative. As for the results obtained regarding the researcher's analysis, it can be concluded that this poem is a poem that has many types based on various points of view of the meaning contained in various types of poetry. This poem is an elegiac poem because it expresses feelings of sadness and contains the poet's lamentations.